Yellow-light carbon dot, preparation method thereof and application of yellow-light carbon dot in light-emitting diode
By synthesizing graphite-like yellow light carbon dots through solvothermal reaction, the problems of unstable emission wavelength, low quantum yield, and poor packaging adaptability of yellow light carbon dots have been solved, achieving stable yellow light emission and improved quantum yield, which is suitable for warm white LEDs.
Patent Information
- Application Number
- CN202511029599.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-31
AI Technical Summary
Existing yellow carbon dots have unstable emission wavelengths, low quantum yields, and poor packaging adaptability, making it difficult to meet the application requirements of warm white LEDs.
Using pyrogallol, thiourea and o-phenylenediamine as raw materials, graphite-like yellow carbon dots were synthesized in an organic solvent via a solvothermal reaction. The particle size was controlled at 1.6-2.9 nm. Combined with centrifugation and filtration, a stable yellow carbon dot solution was prepared and coated onto LED chips as a fluorescence conversion material.
It achieves improved wavelength stability and quantum yield of yellow carbon dots, avoids aggregation and fluorescence quenching problems, enhances the optical stability and lifespan of LED devices, has good packaging adaptability, and is suitable for warm white light lighting.
Smart Images

Figure CN120865907A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optoelectronic materials technology, and more specifically, to a yellow carbon dot, its preparation method, and its application in light-emitting diodes. Background Technology
[0002] Carbon quantum dots are a class of zero-dimensional nanomaterials composed of light elements such as carbon, hydrogen, oxygen, and nitrogen. They possess excellent water solubility, low toxicity, photoluminescence properties, and chemical stability. As an emerging photofunctional material, carbon dots have gained widespread attention in recent years in fields such as bioimaging, photocatalysis, sensing, and optoelectronic devices due to their green synthesis pathway and tunable luminescence behavior.
[0003] To regulate the luminescence properties of carbon dots, researchers have attempted to construct luminescent structures using various carbon sources (such as citric acid, glucose, and amino acids) and dopants (such as nitrogen, sulfur, and phosphorus), and have developed a variety of synthesis techniques, including pyrolysis, microwave methods, laser ablation, and solvothermal reactions. Among these, solvothermal reactions are widely used due to their mild reaction conditions, good structural controllability, and product uniformity. Although the above research has made some progress in blue and green emitting carbon dots, existing yellow emitting carbon dots still generally suffer from the following problems: First, the emission wavelength is too short or the spectral bandwidth is too wide, resulting in low color purity and unstable light color; second, the quantum yield is insufficient, making it difficult to meet the brightness requirements of optoelectronic devices; third, some carbon dots are prone to aggregation, luminescence quenching, or sedimentation after being combined with organic encapsulation resins, seriously affecting the lifespan and stability of devices. In addition, different precursor combinations have a significant impact on the luminescence properties of carbon dots, and how to screen suitable carbon sources and auxiliary agents to construct carbon dot systems with stable yellow light emission properties remains a key research direction.
[0004] Therefore, there is an urgent need to develop a carbon dot material with stable yellow light emission, good quantum yield, and good packaging adaptability to promote the practical application of carbon dots in warm white LEDs. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of the prior art by providing a yellow carbon dot, its preparation method, and its application in light-emitting diodes, thereby solving the problems of unstable emission wavelength, low quantum yield, and poor packaging adaptability of yellow carbon dots in the prior art.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This application provides a yellow carbon dot, which is a graphite-like nanoparticle with a peak value of 574 nm in the fluorescence emission spectrum and a particle size distribution in the range of 1.6-2.9 nm.
[0007] The yellow-light carbon dots of this application are graphite-like nanoparticles with a carbon core rich in conjugated π systems, which helps stabilize π–π* energy level transitions, thus endowing the yellow-light carbon dots with a clear and stable luminescence center. Specifically, the fluorescence emission peak of the yellow-light carbon dots is stably located at 574 nm, and the particle size distribution is controlled within the range of 1.6–2.9 nm. By limiting the fluctuations of quantum confinement effect induced by size distribution, the spectral position drift caused by changes in electronic density of states is reduced, thereby improving the overall luminescence uniformity and wavelength stability of the yellow-light carbon dots, and thus achieving stable yellow light emission performance dominated by structure.
[0008] Furthermore, the yellow carbon dot exhibits two absorption bands in the ultraviolet-visible absorption spectrum, with absorption peaks located in the range of 250-320 nm. This multi-absorption band characteristic reflects the effective absorption capability of the yellow carbon dot for photons in the ultraviolet band, indicating the existence of multiple energy level transition channels within the yellow carbon dot, providing a basic energy absorption path for the excitation process.
[0009] This application also proposes a method for preparing yellow carbon dots, which includes the following steps: S1. Add pyrogallol, thiourea, and o-phenylenediamine to an organic solvent in a certain proportion and dissolve by sonication; S2. Transfer the obtained solution into a high-pressure reactor and place it in an oven for solvothermal reaction under certain temperature and time conditions. S3. After cooling, the reaction product is centrifuged and filtered to obtain a yellow carbon dot solution.
[0010] This application achieves the synergistic construction of carbon source carbonization, heteroatom doping, and luminescent structure regulation in a single step by adding pyrogallic acid, thiourea, and o-phenylenediamine to an organic solvent in a specific mass ratio and carrying out a solvothermal reaction under closed high-temperature conditions. In the reaction, pyrogallic acid, as an aromatic carbon source, helps to construct a stable carbon core framework; o-phenylenediamine introduces a π-electron donor structure, regulating the electron distribution of the luminescent center; and thiourea provides a nitrogen-sulfur dual-doping environment, regulating the energy level structure and luminescent orbital state density. Simultaneously, the organic solvent used possesses good polarity and dispersibility, which facilitates the uniform mixing of reaction intermediates and particle size control, resulting in uniform particle size and ordered structure of the obtained yellow-light carbon dots, providing stable physical support for the luminescent channel. Through the synergistic mechanism of structural optimization and doping regulation, this reaction promotes uniform charge distribution within the carbon core, reduces surface defect state density, thereby suppressing nonradiative transitions and improving the radiative recombination efficiency of excited-state electrons. The overall process is simple to operate, the reaction conditions are mild, and it possesses good process adaptability and scale-up potential. The above reaction pathway not only achieves dual regulation of the particle size and energy level structure of yellow carbon dots, but also helps to improve the quantum yield of yellow carbon dots and enhance their luminous efficiency and long-term stability in light-emitting device applications.
[0011] Furthermore, in S1, the amount of pyrogallic acid is 0.1-0.2 g, the amount of thiourea is 1.0-2.0 g, and the amount of o-phenylenediamine is 1.0-2.0 g. This ratio ensures the formation of the aromatic framework structure while balancing the heteroatom doping ratio, which helps to control the energy level structure and defect density of the yellow carbon dots, thereby optimizing their luminescence performance and stability.
[0012] Furthermore, in S1, the organic solvent is N,N-dimethylformamide (DMF), and the amount of N,N-dimethylformamide used is 5-15 mL. As a highly polar solvent, DMF promotes the complete dissolution and uniform mixing of the precursor, and at the same time participates in the reaction to regulate the carbonization pathway. Adjusting its amount helps to control the particle nucleation rate and the final particle size distribution.
[0013] Furthermore, in S2, the solvothermal reaction temperature is 140-200℃, and the reaction time is 4-8 hours. These reaction conditions balance the reactivity of the precursor with the ordered structure of the carbon core, thereby achieving synergistic control of particle size, structure, and optical properties.
[0014] Furthermore, in S3, the centrifugation speed is 8000-12000 rpm, and the pore size of the filter membrane used in the filtration process is 0.2-0.3 μm. This centrifugation speed generates sufficient centrifugal force within the effective time to rapidly settle larger polymerization byproducts or agglomerated carbon dots in the reaction solution, while avoiding particle structure damage or stability reduction due to excessive rotation speed. The pore size of the filter membrane is located at the micron to submicron level, which can trap residual large particles and unreacted organic matter, ensuring a concentrated final carbon dot particle size distribution. This centrifugation-filtration combined process ensures the acquisition of a stable, highly transparent, yellowish carbon dot solution, providing a fundamental guarantee for the uniform dispersion of the subsequent phosphor and the consistency of device luminescence.
[0015] This application also proposes an application of yellow carbon dots in light-emitting diodes, wherein the yellow carbon dots are coated on the LED chip as a fluorescence conversion material, which is suitable for constructing warm white LED devices.
[0016] The yellow carbon dots prepared in this application possess stable photoluminescence properties, making them suitable for integration into light-emitting diode (LED) devices as fluorescent conversion materials. When placed in the light-emitting path of a short-wavelength LED chip, they emit stable yellow light under excitation light. The unabsorbed excitation light and the yellow light emitted by the carbon dots are superimposed and mixed in space, thereby achieving continuous spectral coverage and a moderate color temperature for warm white light output. Because these yellow carbon dots have a well-defined luminescent center and good wavelength stability, they help improve the uniformity of the emitted color and the optical stability during operation, meeting the requirements for color rendering and lifespan in warm white light lighting applications.
[0017] Furthermore, the yellow carbon dot solution is mixed with epoxy resin AB glue to form a composite phosphor, which is then coated onto the LED chip. This composite method achieves uniform dispersion of the yellow carbon dots in the encapsulation layer, avoiding non-radiative losses caused by agglomeration, while improving the consistency and mechanical stability of the phosphor film formation and enhancing the device's lifespan.
[0018] Furthermore, epoxy resin AB adhesive is a mixture of epoxy resin A and epoxy resin B in a mass ratio of 1:4.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The method for preparing yellow light carbon dots proposed in this application integrates the synergistic effect of three-component precursors with a one-step solvothermal reaction pathway to construct a stable, uniformly luminescent, and well-encapsulated yellow light carbon dot system. This method simplifies the reaction process and reduces the probability of defect formation while achieving carbon source carbonization, heteroatom co-doping, and structural control. The prepared yellow light carbon dots have a particle size concentrated in the range of 1.6-2.9 nm, and the emission peak is stably located at 574 nm, exhibiting good emission consistency and wavelength stability, improving quantum yield and luminescence efficiency, and solving the problems of unstable carbon dot emission, low quantum yield, and insufficient brightness in the prior art.
[0020] (2) The yellow carbon dots of this application have good packaging stability and excitation response characteristics, making them suitable as fluorescent conversion materials coated on the surface of LED chips to achieve stable warm white light output. Their emission spectrum is continuous and their color temperature is moderate, which helps to improve the color rendering and color consistency of the device. Compared with traditional phosphors, these yellow carbon dots avoid problems such as agglomeration and fluorescence quenching, enhance the optical stability and lifespan of the device, and are suitable for high-performance warm white light lighting applications. Attached Figure Description
[0021] Figure 1 A flowchart of a method for preparing yellow carbon dots provided by the present invention; Figure 2 The characterization diagram of the yellow carbon dots of the present invention specifically includes: (a) transmission electron microscope image, (b) high-resolution transmission electron microscope image, and (c) particle size distribution map. Figure 3 The X-ray diffraction pattern of the yellow carbon dots of this invention; Figure 4 This is the ultraviolet-visible absorption spectrum of the yellow carbon dots of this invention; Figure 5 The photoluminescence characteristics of the yellow carbon dots of the present invention are shown in the following diagrams: (a) fluorescence emission spectrum and (b) fluorescence excitation spectrum. Figure 6 This is the infrared spectrum of the yellow carbon dots of the present invention; Figure 7The image shows the effect of the yellow carbon dots of the present invention in light-emitting diodes, specifically including: (a) the image of the chip lit up by the yellow carbon dots coated with the chip, and (b) the CIE1931 chromaticity coordinate diagram of the corresponding device. Detailed Implementation
[0022] To make the implementation process of this invention clearer, a detailed description will be provided below in conjunction with the accompanying drawings.
[0023] Example 1: This invention provides a method for preparing yellow carbon dots, such as... Figure 1 As shown, the method includes the following steps: S1. Add pyrogallic acid, thiourea, and o-phenylenediamine to an organic solvent in a specific ratio and dissolve by sonication; weigh 0.1g of pyrogallic acid, 1g of thiourea, and 1g of o-phenylenediamine and place them in a container, then add 10mL of DMF as a solvent. The mixture is then sonicated for 10 minutes to form a homogeneous and transparent precursor solution.
[0024] In this preparation method, each raw material has the following functional role: Pyrogallic acid (3,4,5-trihydroxybenzoic acid), as a natural polyphenolic compound, contains three adjacent phenolic hydroxyl functional groups in its molecule, possessing strong reducing and antioxidant capabilities, providing a high-density hydroxyl source and aromatic structural framework for subsequent reaction systems; thiourea, a sulfur-containing organic molecule, contains amino and thioamide functional groups in its molecule, releasing active sulfur elements during heat treatment, providing a source for carbon material doping, and also possessing certain complexing and cross-linking potential; o-phenylenediamine, an aromatic amine molecule with two ortho-amino groups in its structure, has a significant π-conjugated structure, high nitrogen atom density, and possesses electron-rich and basic properties, used to construct nitrogen-containing conjugated frameworks or enhance electron density distribution.
[0025] The three raw materials mentioned above have well-defined structures, are widely available, and have low costs, making them suitable for the design and control of subsequent homogeneous reaction systems. Meanwhile, the selected solvent, DMF, is a highly polar organic solvent capable of simultaneously dissolving phenols and amines, exhibiting excellent precursor-dissolving ability. This facilitates the formation of a transparent and homogeneous initial reaction solution and provides a basis for a uniform molecular distribution during subsequent reactions.
[0026] S2. Transfer the obtained solution into a high-pressure reactor and place it in an oven for solvothermal reaction under certain temperature and time conditions; seal the solution obtained in step S1 in the polytetrafluoroethylene liner of the high-pressure reactor and place it in an oven for solvothermal reaction at a set temperature of 180℃ for 6 hours.
[0027] Under these conditions, the three raw materials undergo synergistic carbonization, cross-linking, and heteroatom doping reactions in a high-temperature, sealed environment, gradually constructing a carbon dot structure system with stable yellow light emission performance. The specific reaction process is as follows: First, pyrogallic acid, as the main carbon source, possesses three adjacent phenolic hydroxyl groups in its molecular structure that exhibit strong reducing properties under high-temperature conditions. Compared to ordinary gallic acid, it can dominate the reductive carbonization process of the precursor system in the early stages of the reaction, rapidly generating a carbon core structure. Simultaneously, its polyphenolic structure helps construct a highly ordered aromatic carbon skeleton and inhibits the formation of oxidative defects during the reaction, improving the crystallinity and fluorescence stability of the formed carbon dots. Second, thiourea decomposes under heating conditions, releasing active sulfur-containing groups that undergo a condensation reaction with the ortho-amino group in the o-phenylenediamine molecule, generating benzothiazole-like structural units in situ. This type of structure possesses strong π-conjugation and specific energy level states, which helps to construct luminescent centers with emission wavelengths in the visible yellow light region. Furthermore, the C–S bonds formed in the reaction also enhance the charge transfer efficiency of the carbon dot system, broadening its excitation wavelength response range. Furthermore, o-phenylenediamine molecules provide a nitrogen source, and their aromatic amine structure participates in the conjugation of carbon dot carbon nuclei to form an electron-rich π system. Together with the synergistic doping of sulfur, they regulate the band structure and surface state density of carbon dots, making it easier for excited state electrons to achieve radiative transitions, thereby achieving a redshift in luminescence behavior and an improvement in luminescence efficiency.
[0028] The three precursors exhibit a clear synergistic ratio and reaction pathway, and none can be omitted. Pyrogallic acid dominates carbon nucleation and framework stabilization; thiourea and o-phenylenediamine jointly participate in doping and heterocycle construction. Compared to single- or two-component systems, this three-component system initially constructs carbon dot structures with yellow light emission capability.
[0029] This embodiment employs a solvothermal reaction at 180℃ for 6 hours to achieve efficient carbonization, condensation, and heteroatom synergistic doping of the three-component system. This ensures the ordered structure of the carbon core and the stable construction of the luminescent centers, while also controlling the energy level state and particle size distribution on the carbon dot surface. The selected temperature facilitates the full reaction of the precursors while suppressing structural defects and particle agglomeration caused by excessively high temperatures. The reaction time is controlled within 6 hours to prevent excessive particle size growth while ensuring sufficient reaction, thereby improving the luminescence efficiency and wavelength stability of the reaction products. Compared to conventional carbon dot synthesis methods, this combination of reaction parameters shortens the synthesis cycle, improves production efficiency and energy consumption control, and exhibits good controllability and repeatability, making it suitable for large-scale preparation of stable yellow luminescent carbon dot materials.
[0030] S3. After cooling, the reaction product is centrifuged and filtered to obtain a yellow carbon dot solution. After the solvothermal reaction is complete, it is naturally cooled to room temperature. The resulting mixture is a dark brown transparent solution containing the target yellow carbon dots, unreacted organic residues, and possible polymerization byproducts. To remove large particulate impurities and obtain a well-dispersed yellow carbon dot solution, a combination of centrifugation and filtration is used for post-treatment. Specifically, the reaction solution is centrifuged at 11,000 rpm for 15 minutes to initially separate insoluble large particles and polymer precipitates. Then, it is filtered three times using a disposable injection-type microfiltration membrane with a pore size of 0.22 μm to further remove impurities larger than micrometers and possible residual macromolecular precursors, thereby obtaining a transparent and stable yellow carbon dot dispersion with a narrow particle size distribution.
[0031] Subsequent processing steps ensure the structural purity and optical consistency of the carbon dot products, which is beneficial to improving their reliability in characterization analysis and device integration. The resulting solution can be directly used for subsequent photophysical characterization such as ultraviolet absorption, fluorescence emission, and particle size distribution. It can also be loaded into light-emitting diode devices by spin coating, spraying, etc., to achieve stable yellow light emission or warm white light output.
[0032] The yellow-light carbon dots prepared in this embodiment are graphite-like nanoparticles with a layered carbon core configuration. This structural type facilitates the formation of a stable conjugated system, providing a fundamental support for subsequent luminescence behavior. The particle size distribution of the yellow-light carbon dots ranges from 1.6 to 2.9 nm, and the particle size control within the nanoscale range is beneficial for unifying their band structure and reducing luminescence differences caused by size distribution. The peak value of the yellow-light carbon dots in the fluorescence emission spectrum is located at 574 nm, which belongs to the yellow light band in the visible light region, exhibiting certain wavelength stability and luminescence intensity. Furthermore, in the ultraviolet-visible absorption spectrum, the yellow-light carbon dots exhibit two main absorption bands in the 250-320 nm range, indicating that they possess strong ultraviolet light absorption capabilities, providing primary energy support for subsequent excitation behavior.
[0033] To further verify the structural characteristics and optical properties of the prepared yellow carbon dots, the yellow carbon dots obtained in this embodiment were systematically characterized. The characterization results are as follows: Figures 2-6 As shown.
[0034] like Figure 2 As shown, the yellow carbon dots were observed by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM), and the results were analyzed in combination with the particle size statistics to clarify the morphology and particle size distribution of the yellow carbon dots. Figure 2 (a) is an image shown by transmission electron microscopy. The image shows that the yellow carbon dots are generally spherical in shape, with clear particle edges and uniform particle size distribution. No obvious agglomeration was observed, indicating that the nucleation and growth process of particles was well controlled during the reaction. Figure 2 (b) is an image shown by a high-resolution transmission electron microscope. Obvious lattice fringes with a spacing of 0.218 nm are observed in the image, which belong to the graphene (100) crystal plane. This result indicates that the prepared yellow carbon dots have a certain degree of crystallinity and exhibit a graphite-like structure, which helps to improve their optical stability and electron transport performance. Figure 2 (c) is a particle size distribution diagram. The results show that the particle size of the yellow carbon dots is mainly concentrated in 1.6-2.9 nm, with an average particle size of 2.15 nm. This indicates that the three-component system and mild reaction conditions can achieve the construction of nanostructures with good size controllability.
[0035] To further verify the crystal structure type and degree of order of the yellow carbon dots, X-ray diffraction (XRD) analysis was performed on them, such as... Figure 3 As shown. Figure 3 A distinct broad peak appears at 21°, representing the diffraction signal of the amorphous graphite layer structure, indicating that the prepared yellow carbon dots mainly have a graphite-like structure with randomly stacked carbon nuclei inside. No obvious impurity peaks were observed in the spectrum, indicating that this method yields products with high structural purity. This structural feature helps stabilize the luminescent center and ensures its structural integrity during optoelectronic applications.
[0036] Furthermore, to investigate the light absorption capacity of the yellow carbon dots, ultraviolet-visible absorption measurements were performed, and the absorption spectrum is shown below. Figure 4 As shown in the figure, the yellow carbon dot exhibits two distinct absorption bands in the 250-320 nm range. The shorter, high-energy absorption band is attributed to π–π* transitions in the aromatic structure, while the longer, low-energy absorption band is related to n–π* transitions of nitrogen- or oxygen-containing groups on the surface. This dual absorption behavior reflects that the yellow carbon dot possesses multiple electronic transition pathways, providing a primary energy absorption basis for subsequent excitation behavior; however, its true effective excitation wavelength requires further analysis using fluorescence excitation spectroscopy.
[0037] The fluorescence emission and excitation spectra of the yellow carbon dots were measured to evaluate their luminescent properties. The results are as follows: Figure 5 As shown. Figure 5 (a) The fluorescence emission spectra measured under six different excitation wavelengths (Ex=440nm, 450nm, 460nm, 470nm, 480nm, and 490nm). The results show that under all excitation wavelengths, the yellow carbon dot exhibits a main emission peak at 574nm, and the peak positions of each curve are consistent and the spectral shape is symmetrical, indicating that its luminescent center structure is stable, the energy level distribution is uniform, and there is no excitation dependence. Among them, the emission intensity reaches the maximum under the condition of Ex=470nm, indicating that this band has good matching with its excitation channel and has high excitation efficiency. Figure 5(b) shows the fluorescence excitation spectrum measured under a fixed emission wavelength of 574 nm. The results show that the yellow carbon dot exhibits a significant excitation response in the 330-500 nm range, with a broad wavelength characteristic covering the ultraviolet to blue light region, reflecting the strong excitation light adaptability of the yellow carbon dot. The response intensity in the excitation spectrum reaches a relative maximum in the 440-480 nm range, indicating that the yellow carbon dot has high excitation efficiency in the blue light band. This characteristic further proves its suitability for fluorescence conversion applications under short-wavelength LED excitation, demonstrating its feasibility for integration into UV or blue light-excited LED devices.
[0038] To determine the surface chemical composition and functional group types of the yellow carbon dots, Fourier transform infrared spectroscopy (FTIR) analysis was performed. The results are as follows: Figure 6 As shown in the figure. At 3145cm -1 The presence of a distinct absorption peak at 1654 cm⁻¹ is attributed to the –OH / N–H stretching vibration, indicating the presence of hydroxyl or amino structures on the surface of the yellow carbon dots; -1 The absorption peak corresponds to the stretching vibration of the C=O bond, indicating the formation of amide or carboxyl functional groups during the reaction; 1103 cm⁻¹ -1 The characteristic peaks are attributed to the stretching vibrations of the C–O bond, suggesting the presence of ether bonds or hydroxyl groups in the molecule. (2815 cm⁻¹) -1 With 1394cm -1 The vibrations at these locations are attributed to stretching vibrations of C–H and C–N bonds, respectively, indicating the presence of hydrocarbon and nitrogen heterostructures on the surface of the yellow carbon dots. Additionally, at 2059 cm⁻¹... -1 Absorption peaks of the C≡C triple bond were observed, indicating the presence of a small amount of alkyne structures or conjugated π systems in the system. In summary, the surface of this yellow carbon dot is rich in oxygen- and nitrogen-containing functional groups, which helps to improve its water solubility, interfacial activity, and optical stability. Furthermore, the electronic effects of these functional groups also help to stabilize the luminescent center, improving its structural consistency and luminescence reliability during application.
[0039] Example 2: Based on Example 1, to further improve the particle size uniformity and luminescence performance consistency of the yellow carbon dots, this example uses microwave heating instead of traditional oven heating, and introduces a staged temperature control design to synergistically optimize the nucleation and growth process of the yellow carbon dots. Specifically, 0.1g of pyrogallol, 1g of thiourea, and 1g of o-phenylenediamine are added to 10mL of LDMF and sonicated at room temperature for 10 minutes to form a precursor mixture solution. This solution is transferred to the polytetrafluoroethylene liner of a microwave synthesis reactor, and the microwave heating program is set to proceed in two stages: the first stage is pretreatment at 120°C for 30 minutes to induce preliminary cross-linking between precursors and the formation of intermediates; the second stage is heating to 180°C for 4 hours to drive the carbonization reaction and the directional formation of doped structures. After the reaction is completed, the mixture is naturally cooled to room temperature, and the resulting product is centrifuged at 11,000 rpm for 15 minutes and filtered through a 0.22μm filter membrane to obtain a homogeneous yellow carbon dot solution.
[0040] The microwave heating method in this embodiment achieves rapid and uniform heating of the reaction system, avoiding the temperature gradient and uneven thermal stress phenomena present in traditional heat conduction methods, which is conducive to the formation of carbon core structures with uniform particle size. At the same time, microwave radiation can excite polar molecules (such as DMF and amine precursors) to produce directional vibrations, promote the reactivity between precursors, and improve the carbon source carbonization rate and heteroatom introduction efficiency.
[0041] This staged temperature-controlled reaction design aims to regulate the time window for carbon dot nucleation and carbon nucleus growth. The first stage, a uniform pre-reaction under medium-temperature conditions, induces stable complexation and preliminary cross-linking reactions between the aromatic carbon source and amino and thiourea molecules, avoiding structural disorder or aggregation caused by intense exothermic reactions, while simultaneously promoting the uniform formation of primary carbon nuclei. The second stage, a high-temperature treatment, accelerates the carbonization process, promotes the orderly growth of carbon nuclei, and drives the stable doping of nitrogen- and sulfur-containing functional groups, helping to control the energy level structure, luminescent center density, and surface state energy level arrangement of the carbon dots.
[0042] This strategy synergistically utilizes microwave excitation and staged reaction control to construct structurally ordered, uniformly sized yellow carbon dots within a short reaction time. This helps improve π–π* transition efficiency, reduce emission instability caused by quantum confinement effect fluctuations, and enhance the uniformity of the luminescent center structure, thereby improving the quantum yield of the yellow carbon dots and their optical stability in LED device applications.
[0043] Example 3: This application also proposes an application of yellow carbon dots in light-emitting diodes (LEDs). The yellow carbon dots are coated onto the LED chip as a fluorescence conversion material, suitable for constructing warm white LED devices. The "application in light-emitting diodes" described in this application specifically refers to coating yellow carbon dots onto the surface of an LED chip as a fluorescence conversion material, achieving warm white light output through LED chip excitation, without involving any modification to the structure of the LED chip itself.
[0044] In optoelectronic applications, rare-earth-doped phosphors are commonly used as conversion materials for white LED lighting. However, the limited distribution and high extraction cost of rare-earth resources, coupled with insufficient red light efficiency, restrict their further development in the high color rendering index (CRI) warm white light direction, which is particularly unfavorable for lighting scenarios with low power consumption and high environmental protection requirements. Therefore, this embodiment uses the yellow carbon dots prepared in Example 1 as an alternative phosphor conversion material. These yellow carbon dots possess characteristics such as concentrated particle size distribution, stable emission wavelength, and good excitation response, allowing them to be directly applied to the fabrication of warm white LEDs without complex surface modification. Furthermore, the yellow carbon dots are obtained through low-temperature liquid-phase synthesis, avoiding the thermal stress and energy consumption problems caused by high-temperature sintering of rare-earth materials. Since their structure does not contain heavy metal elements and exhibits high luminescence stability, they possess good potential as a substitute for rare-earth phosphors.
[0045] In this specific application, a yellow carbon dot solution is mixed with epoxy resin to form a stable and uniform composite phosphor. This composite phosphor is applied to the light-emitting surface of the LED chip using methods such as drop coating, spin coating, or spraying to form a fully covered phosphor layer. Subsequently, a thermosetting or room-temperature curing process is used to cross-link the composite phosphor onto the LED chip surface, thereby firmly embedding the yellow carbon dots into the encapsulation layer and integrating them with the excitation light path. The entire encapsulation process is gentle and will not cause thermal damage to the LED chip structure. Furthermore, the resulting phosphor layer exhibits excellent optical uniformity and mechanical adhesion. This method not only simplifies the encapsulation process but also avoids the problem of yellow carbon dots agglomerating in the colloid to form non-radiative centers, improving light conversion efficiency and luminescence consistency. Moreover, the yellow carbon dots use pyrogallic acid as one of their carbon sources, naturally possessing antioxidant and anti-photobleaching capabilities, allowing the phosphor layer to maintain stable luminescence intensity and color tone under long-term light excitation, thus improving the lifespan and reliability of the LED device. The encapsulated phosphor layer stably emits yellow light under short-wavelength excitation such as ultraviolet or blue light. The yellow light mixes with the residual excitation light of the LED chip in space to achieve warm white light output. It has good spectral coverage and color temperature control capabilities, and is suitable for various scenarios such as residential lighting, flexible displays and low-power light emission.
[0046] To achieve stable dispersion and efficient light emission of the yellow carbon dots in light-emitting diode devices, this embodiment uses epoxy resin AB adhesive as the encapsulation matrix. Epoxy resin AB adhesive is a mixture of epoxy resin A and epoxy resin B in a 1:4 mass ratio. Epoxy resin A is the main agent, containing bisphenol A type epoxy resin or modified epoxy prepolymer main chain structural units, responsible for providing the crosslinking network framework and film-forming properties. Epoxy resin B is the curing agent, an aliphatic or aromatic amine such as polyamide, isophorone diamine (IPDA), or polyetheramine, which initiates the crosslinking reaction to form a dense solid resin matrix.
[0047] In this embodiment, the mixing scheme is as follows: first, epoxy resin A and epoxy resin B are mixed in a certain proportion to form epoxy resin AB, and then the resulting epoxy resin AB is mixed evenly with the yellow carbon dot solution prepared in Example 1 to form a composite fluorescent adhesive. This scheme is simple to operate, avoids direct contact between the yellow carbon dots and highly active groups, reduces the risk of aggregation and fluorescence quenching, and ensures that they are uniformly dispersed and stably emit light in the crosslinked network.
[0048] Considering the differences in surface structure, solvent system, or target device structure of different carbon dots, other mixing methods can be selected as needed during the actual packaging process to expand the scope of technology application, including: (1) premixing the carbon dot solution with epoxy resin A and then introducing epoxy resin B for curing; suitable for situations where the functional groups on the carbon dot surface are weak and do not easily participate in cross-linking reactions, thus improving its dispersion uniformity. (2) premixing the carbon dot solution with epoxy resin B and then adding epoxy resin A; suitable for scenarios where the carbon dots have good stability in the curing agent environment or where the carbon dot surface needs to be modified by coupling using amine structures. (3) dispersing the carbon dot solution in epoxy resin A and epoxy resin B respectively, and then mixing and reacting simultaneously; this method is beneficial to maximize the contact uniformity between the carbon dots and the system interface, and is suitable for high-performance devices with high requirements for luminescence uniformity.
[0049] The above four mixing methods can be flexibly selected according to the characteristics of the surface groups of carbon dots, the type of dispersion medium and the requirements of the encapsulation process, so as to build a stable and efficient fluorescent composite system and improve the encapsulation adaptability and luminous performance of carbon dots in LED devices.
[0050] To verify the luminescence effect of the yellow carbon dots in the LED device in this embodiment, a UV LED chip with a main peak wavelength of 365nm was selected as the excitation source. The yellow carbon dot solution prepared in Example 1 was mixed with epoxy resin AB glue and stirred thoroughly to form a uniform composite phosphor. The composite phosphor was applied to the light-emitting surface of the UV LED chip by spin coating to form a uniform coating. After curing at 80-100℃ for 30-60 minutes, a fixed yellow carbon dot phosphor layer was obtained. The packaged LED device was tested under power supply. After lighting, a uniform and stable yellow fluorescence was observed in the excitation area of the LED chip. Figure 7 As shown in (a), this figure demonstrates the direct luminescence effect of the yellow carbon dots under 365nm excitation light, indicating that the yellow carbon dots are well matched with the excitation wavelength and have stable photoluminescence capabilities; moreover, the coating is continuous and there are no obvious light spots or local dark areas, verifying that the composite fluorescent adhesive has good dispersibility and high optical uniformity after curing.
[0051] Furthermore, the luminous performance of LED devices was evaluated using CIE 1931 colorimetric analysis. The light emitted by the LED devices was collected using an integrating sphere and sent to the CIE colorimetric analysis system for coordinate positioning, such as... Figure 7 As shown in (b), the chromaticity coordinates obtained in the figure are (0.368, 0.362), which are located near the Planck locus in the CIE1931 chromaticity diagram, and the corresponding correlated color temperature is 4100K. The light color represented by this coordinate point belongs to the typical warm white light range, which has good human eye comfort and color reproduction ability, and is suitable for indoor ambient lighting and display lighting.
[0052] The above experiments verify that the yellow carbon dots of this application have good luminescence response and color modulation ability under ultraviolet excitation, and further confirm the adaptability and feasibility of this embodiment in warm white LED applications.
[0053] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A type of yellowish carbon dot, characterized in that: The yellow carbon dots are graphite-like nanoparticles with a peak value of 574 nm in the fluorescence emission spectrum and a particle size distribution in the range of 1.6-2.9 nm.
2. The yellowish carbon dots according to claim 1, characterized in that: The yellow carbon dots have two absorption bands in the ultraviolet-visible absorption spectrum, with absorption peaks located in the range of 250-320 nm.
3. A method for preparing yellowish carbon dots, characterized in that: The method includes the following steps: S1. Add pyrogallol, thiourea, and o-phenylenediamine to an organic solvent in a certain proportion and dissolve by sonication; S2. Transfer the obtained solution into a high-pressure reactor and place it in an oven for solvothermal reaction under certain temperature and time conditions. S3. After cooling, the reaction product is centrifuged and filtered to obtain the yellow carbon dot solution.
4. The method for preparing yellow carbon dots according to claim 3, characterized in that: In S1, the amount of pyrogallic acid is 0.1-0.2g, the amount of thiourea is 1.0-2.0g, and the amount of o-phenylenediamine is 1.0-2.0g.
5. The method for preparing yellow carbon dots according to claim 4, characterized in that: In S1, the organic solvent is N,N-dimethylformamide, and the amount of N,N-dimethylformamide used is 5-15 mL.
6. The method for preparing yellow carbon dots according to claim 5, characterized in that: In S2, the reaction temperature of the solvothermal reaction is 140-200℃, and the reaction time is 4-8 hours.
7. The method for preparing yellow carbon dots according to claim 6, characterized in that: In S3, the centrifugation speed is 8000-12000 rpm, and the pore size of the filter membrane used in the filtration process is 0.2-0.3 μm.
8. An application of a yellow carbon dot in a light-emitting diode, characterized in that: The yellow carbon dots are coated onto the LED chip as a fluorescence conversion material, which is suitable for constructing warm white LED devices.
9. The application of the yellow carbon dots according to claim 8 in a light-emitting diode, characterized in that: The yellow carbon dot solution is mixed with epoxy resin AB glue to form a composite fluorescent adhesive, which is then coated onto the LED chip.
10. The application of the yellow carbon dots according to claim 9 in a light-emitting diode, characterized in that: The epoxy resin AB adhesive is a mixture of epoxy resin A and epoxy resin B in a mass ratio of 1:4.